CIGARETTE SMOKE AND THE NONSMOKER ISSUE ANALYSIS AND PROGRAM RECOMMENDATIONS (Tufts Archival Research Center, 2007)
Confidential; Draft of an issue analysis and program recommendations entitled “Smoking and the Non-Smoker.” Reports that opposition to public smoking has little scientific evidence to claim that secondhand smoke has negative health effects. Acknowledges that public support of smokers has dwindled over the past few years. Broadens issue of Environmental Tobacco Smoke (ETS) to include the overall air quality in buildings. Analyzes reasons that the tobacco industry is unable to influence public opinion on the issue of ETS. Recommends several new strategies be adopted.